Pengaruh disiplin kerja dan gaya kepemimpinan terhadap kinerja karyawan PT. Kalibata sarana distrindo di Jabodetabek - Abidin, Ali Zaenal; Falah, Prangi Nurul (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of work discipline and leadership style on employee performance at PT. Kalibata Sarana Distrindo partially or simultaneously. The research method used in this study is quantitative research and data collection with questionnaire techniques, the number of samples used in this study were 46 respondents. The variables used in this study were tested using statistical tests which included validity tests, reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, multiple linear regression equations, correlation coefficients, coefficients of determination, t-test and F-test. Partial T-test shows that there is a significant effect of Work Discipline on Employee Performance of PT. Kalibata Sarana Distrindo in Jabodetabek, and there is a significant effect of Leadership Style on employee performance of PT. Kalibata Sarana Distrindo in Jabodetabek. Based on the simultaneous F test that there is an effect Variables of Work Discipline and Leadership Style on Employee Performance at PT. Kalibata Sarana Distrindo in Jabodetabek.